Modelos de enseñanza secundaria obligatoria en Europa - Pedró, Francesc (Revista Española de Pedagogía, 2018)
Although there is a broad diversity in European secondary education, it seems to be that a common trend is clear, namely that of comprehensivity at the lower level and diversification at the upper level. This trend raises the issue of the nature of the debates implied: are they strictly pedagogical or political? Be that as it may, the article focuses on the exemplification of this common trend throughout different European systems and shows a number of reasons which support its widespread acceptance. At the same time, it also discusses some cases where the comprehensive principle seems to have been rejected.
Keywords: enseñanza secundaria obligatoria; Europa; Revista Española de Pedagogía